Real‐Time PCR Assay and Environmental DNA Workflow for Detecting Irukandji Jellyfish, Malo bella (Cubozoa) - Jessica K. Strickland; Kylie A. Pitt; Michael J. Kingsford; Scott J. Morrissey; Dean R. Jerry (Environmental DNA)
ABSTRACT The rise in coastal populations and marine activities has intensified challenges posed by hazardous Irukandji jellyfishes, whose stings can cause severe symptoms and sometimes death. Despite their significant impact on health services and marine‐related industries, Irukandji jellyfishes remain poorly understood due to the challenges of studying them and the limitations of traditional sampling methods. Genetic methods and environmental DNA (eDNA) offer promising solutions. This study developed and validated a sensitive and specific quantitative PCR assay to detect and monitor Malo bella, an Irukandji jellyfish threatening tourism in Western Australia. M. bella‐specific primers and a TaqMan Minor Groove Binding (MGB) probe were designed. The assay demonstrated high specificity, not amplifying non‐target species, and sensitivity, with 95.6% efficiency, a slope of −3.43, and an R2 value of 0.98. The assay's 95% limit of detection (LoD) was 0.80 eDNA copies/reaction, and the modeled limit of quantification (LoQ) was 13 eDNA copies/reaction. Validation through in silico and in vitro tests confirmed successful detection of M. bella eDNA in all water samples from aquaria and around medusae in the ocean. Sanger sequencing verified the amplification of the target M. bella sequence. This assay improves the ability to study M. bella, addressing critical knowledge gaps on the species' ecology. These include assessing the spatial and temporal distributions of this species and potential detection of early benthic life stages to identify source populations. Such studies will improve management of envenomation risks in tourism hotspots. Future research should explore integrating passive or automated samplers and developing real‐time detection assays to further enhance monitoring capabilities and mitigate risks posed by hazardous marine species.